Factors Associated with Vulnerability to HIV and Sexually Transmitted Infections among Street Children in Selected Towns of Ethiopia, 2016 (2017)
Background: The problem of street children is becoming a world crosscut ting issue since these children exist in every part of the world and become a worldwide problem. Objective: To assess factors associated with vulnerability to STIs and HIV/AIDS among street children in selected towns of Ethiopia. Methodology: Community-based cross-sectional descriptive study de sign was used on the three selected towns of Ethiopia from June-September, 2016. A total of 360 street children were selected, using snow ball sampling technique. Data were collected using pre-tested interviewer-administered questionnaire. Logistic regression was used to analyze the data. Results: A total of 360 (97.8%) respondents were included in this study. Among them, 167 (46.4%) of them had practiced sexual intercourse and out of these, 137 (82%) had started having sex at the age of 16 years old. Out of these, 61 (36.53%) of them started to get daily basic needs whereas 54 (32.3%) of them were forcefully raped on the street. Only 53 (59.6%) had used condom consistently and 83 (49.7%) had conducted survival sex within the last 12 months. Children on the street or chewing khat or consumption of alcohol had more vulnerability to STIs and HIV about 2.532 (1.57 - 4.08), 2.32 (1.11 - 4.80), 4.18 (2.31 - 7.55) times respectively. But those enrolled in school were about 0.40 (0.25, 0.64) less likely vulnerable than their counterparts. Conclusion: Street children are at a higher likelihood of vulnerability to STIs and HIV. Intervention targeted multilevel approach such as re-integration with their family, life skills training, sexuality education, creating income-generating activities and information education about STIs.